Prevention of Mother-to-Child Transmission (PMTCT): Advancing Strategies to Reduce Infant Mortality - Adumashi, Funke Abolade; Obohwemu, Kennedy Oberhiri; Abayomi, Gabriel Olaoluwa; Kenneth, Iyevhobu Oshiokhayamhe (Advances in Social Sciences Research Journal, 2026)
Mother to child transmission of HIV remains one of the most persistent challenges in global public health, and Nigeria continues to carry a disproportionate share of the burden. This paper reviews the development of prevention of mother to child transmission programmes in Nigeria and examines their progress through a health systems perspective. The analysis draws together evidence on the scale of vertical transmission, the evolution of national policies, and the practical realities that shape service delivery. Although antiretroviral therapy has transformed the prospects of infants born to mothers living with HIV, the Nigerian experience shows that clinical effectiveness alone is not enough to secure population level gains. Weak health systems, uneven access to antenatal care, shortages of trained personnel, gaps in counselling and follow up, and persistent social stigma continue to limit the reach and impact of prevention efforts. The review highlights how these structural constraints interact with individual level factors to influence uptake of testing, adherence to treatment, and infant feeding decisions. It also considers the implications of global targets for elimination of paediatric HIV and the extent to which current strategies align with these ambitions. The paper argues that meaningful progress will require sustained political commitment, stronger integration of prevention services within routine maternal and child health care, and investment in community-based support systems that address the social and economic conditions shaping women’s choices. The review concludes by outlining practical and contextually grounded recommendations that can support Nigeria’s efforts to reduce new paediatric infections and improve HIV free survival.